Wage bargaining in Germany: The role of works councils and opening clauses - Peter Ellguth; Hans-Dieter Gerner; Jens Stegmaier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
German employment relations are characterized by a distinct dual system: First, working conditions and wages are determined by industry level collective bargaining agreements. Second, on the establishment level the works council is responsible for employer-employee negotiations. But since the mid-1980s more and more areas of regulation were transferred from the industry to the establishment level using so called opening-clauses. Our analysis relies on rich German establishment data and reveals new insights in the institutional machinery of wage bargaining: While the existence of such clauses is related to higher wages (11 %), their application results in wages cuts of roughly the same size. Regarding works councils our results suggest that they are able to prevent negative wage effects of opening clauses on average. – – Das deutsche System der industriellen Beziehungen ist durch einen charakteristischen Dualismus gekennzeichnet: Einerseits werden in überbetrieblichen, sektoralen Tarifverträgen Arbeitsbedingungen und Löhne vereinbart. Andererseits regelt der Betriebsrat auf betrieblicher Ebene den Interessensausgleich zwischen Belegschaft und Betriebsführung. Seit Mitte der 1980er-Jahre wurden im Rahmen von Öffnungsklauseln jedoch zunehmend tarifvertragliche Regelungen auf betrieblicher Ebene verändert. Unsere Analysen basieren auf den Daten des IAB-Betriebspanels und gestatten einen besseren Einblick in die institutionellen Mechanismen der Lohnfindung. Wie sich zeigt, geht die Existenz von Öffnungsklauseln in Branchentarifverträgen mit einem höheren Lohnniveau (11 %) einher, deren betrieblicher Einsatz führt hingegen zu einer Lohnreduktion in ungefähr gleichem Ausmaß. Darüber hinaus legen unsere Ergebnisse den Schluss nahe, dass Betriebsräte in der Lage sind, die negativen Lohneffekte von Öffnungsklauseln zu verhindern.
Keywords: J53; J31; 330; works council; worker participation; opening clauses; wages; collective bargaining agreements; organized decentralization; Lohnverhandlungen; Firmentarifvertrag; Tarifvertrag; Deregulierung; Betriebsrat; Deutschland